Mechanism of Huangqi–Honghua combination regulating the gut microbiota to affect bile acid metabolism towards preventing cerebral ischaemia–reperfusion injury in rats - Kai Wang; Yue Chen; Jinyi Cao; Ruimin Liang; Yi Qiao; Likun Ding; Xiaojuan Yang; Zhifu Yang (Pharmaceutical Biology, 2022)
Context Effective treatment of ischaemic stroke is required to combat its high prevalence and incidence. Although the combination of Astragalus membranaeus (Fisch.) Bge. (Fabaceae) and Carthamus tinctorius L. (Asteraceae) is used in traditional Chinese medicine for the treatment of stroke, its underlying mechanism remains unclear.Objective The objective of this study is to elucidate the mechanism underlying Huangqi-Honghua (HQ-HH) for the treatment of ischaemic stroke by gut microbiota analysis and metabonomics.Materials and methods Sprague–Dawley rats were randomly assigned to the sham, model, HQ-HH, and Naoxintong (NXT) groups. The middle cerebral artery occlusion-reperfusion model was established after 7 days of intragastric administration in the HQ-HH (4.5 g/kg, qd) and NXT (1.0 g/kg, qd) groups. The neurological examination, infarct volume, gut microbiota, bile acids, and inflammation markers were assessed after 72 h of reperfusion.Results Compared with the model group, HQ-HH significantly reduced the neurological deficit scores of the model rats (2.0 ± 0.2 vs. 3.16 ± 0.56), and reduced the cerebral infarct volume (27.83 ± 3.95 vs. 45.17 ± 2.75), and reduced the rate of necrotic neurons (26.35 ± 4.37 vs. 53.50 ± 9.61). HQ-HH regulating gut microbiota, activating the bile acid receptor FXR, maintaining the homeostasis of bile acid, reducing Th17 cells and increasing Treg cells in the rat brain, reducing the inflammatory response, and improving cerebral ischaemia–reperfusion injury.Conclusions These data indicate that HQ-HH combination can improve ischaemic stroke by regulating the gut microbiota to affect bile acid metabolism, providing experimental evidence for the wide application of HQ-HH in clinical practice of ischaemic stroke.